Late-Pregnancy Fetal Hypoxia Is Associated With Altered Glucose Metabolism and Adiposity in Young Adult Offspring of Women With Type 1 Diabetes - Klemetti, Miira M.; Teramo, Kari; Kautiainen, Hannu; Wasenius, Niko; Eriksson, Johan G.; Laine, Merja K. (Frontiers in Endocrinology, 2021)
Objective To investigate associations between exposure to fetal hypoxia and indicators of metabolic health in young adult offspring of women with type 1 diabetes (OT1D). Methods 156 OT1D born between 7/1995 and 12/2000 at Helsinki University Hospital, Finland, were invited for follow-up between 3/2019 and 11/2019. A control group of 442 adults born from non-diabetic pregnancies, matched for date and place of birth, was obtained from the Finnish Medical Birth Register. In total, 58 OT1D and 86 controls agreed to participate. All OT1D had amniotic fluid (AF) sampled for erythropoietin (EPO) measurement within two days before delivery in order to diagnose fetal hypoxia. In total, 29 OTID had an AF EPO concentration <14.0 mU/l, defined as normal, and were categorized into the low EPO (L-EPO) group. The remaining 29 OT1D had AF EPO ≥14.0 mU/ml, defined as fetal hypoxia, and were categorized into the high EPO (H-EPO) group. At the age of 18-23 years, participants underwent a 2-h 75g oral glucose tolerance test (OGTT) in addition to height, weight, waist circumference, body composition, blood pressure, HbA1c, cholesterol, triglyceride, high-sensitivity CRP and leisure-time physical activity measurements. Results Two OT1D were diagnosed with diabetes and excluded from further analyses. At young adult age, OT1D in the H-EPO group had a higher BMI than those in the L-EPO group. In addition, among female participants, waist circumference and body fat percentage were highest in the H-EPO group. In the OGTTs, the mean (SD) 2-h post-load plasma glucose (mmol/L) was higher in the H-EPO [6.50 (2.11)] than in the L-EPO [5.21 (1.10)] or control [5.67 (1.48)] offspring (p=0.009). AF EPO concentrations correlated positively with 2-h post-load plasma glucose [r=0.35 (95% CI: 0.07 to 0.62)] and serum insulin [r=0.44 (95% CI: 0.14 to 0.69)] concentrations, even after adjusting for maternal BMI, birth weight z-score, gestational age at birth and adult BMI. Control, L-EPO and H-EPO groups did not differ with regards to other assessed parameters. Conclusions High AF EPO concentrations in late pregnancy, indicating fetal hypoxia, are associated with increased adiposity and elevated post-load glucose and insulin concentrations in young adult OT1D.